Ecosystem Metabolism and Carbon Balance in Chesapeake Bay: A 30‐Year Analysis Using a Coupled Hydrodynamic‐Biogeochemical Model. Issue 8 (23rd August 2019) - Shen, Chunqi; Testa, Jeremy M.; Ni, Wenfei; Cai, Wei‐Jun; Li, Ming; Kemp, W. Michael
Abstract: The carbon cycle in estuarine environments is difficult to quantify because of substantial spatiotemporal heterogeneity in the sources, exchanges, and fates of carbon. We overcame these challenges with a multidecade numerical modeling analysis of seasonal, interannual, and decadal variability in net ecosystem metabolism (NEM) and associated carbon fluxes in Chesapeake Bay. Interannual variability in NEM along the estuarine axis indicated a clear spatial dependency of NEM on riverine discharge, with elevated flows causing increasing upper bay heterotrophy and increasing lower bay autotrophy during wet years. Our 30‐year simulation suggested the Chesapeake Bay is somewhat unique among estuaries in its tendency toward net autotrophy as a consequence of its extremely high nutrient to organic matter input ratio and large size. Budgets of three different carbon pools revealed that the entire Chesapeake Bay is a CO2 source to the atmosphere and organic carbon source to the open shelf, providing quantitative export estimates for interpretation of anthropogenic perturbations to the regional carbon flux. Key Points: A clear spatial dependency of net ecosystem metabolism on river flow was observed in Chesapeake Bay The Chesapeake Bay is unique in its tendency toward net autotrophy due to its extremely high nutrient to organic matter input ratio This study provides key quantitative export estimates for the interpretation of anthropogenic perturbations to the regional carbon flux